(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Introduction: Avian bites, though uncommon, can lead to severe or even life-threatening consequences. Birds can trans mit harmful microorganisms, including Escherichia coli, Staphylococcus aureus, and Candida, through their beaks and talons, potentially leading to sepsis. Sepsis is a systemic inflammatory response to infection that can cause organ failure and death if untreated. Other serious infections, such as cellulitis, abscess, and septicaemia, can also arise, characterized by systemic inflammation, organ dysfunction, and cardiovascular instability. Case Details: We present a rare case of sepsis following a hen bite in a 60-year-old female. The patient developed severe septic shock after being bitten on the right forearm, experiencing significant swelling and episodes of fever. Cellulitis was observed in the affected area, and further assessment confirmed sepsis, acute kidney injury, tachycardia, and tachypnoea. Discussion: Delayed presentation and inadequate initial treatment contributed to the fatal outcome, emphasizing the need for public awareness and education on proper wound care and hygiene following such incidents. Conclusion: Hen bite-induced sepsis, while rare, can be lethal. This case underscores the importance of prompt recogni tion and aggressive management of avian bites, particularly in vulnerable individuals. Despite advances in medical care, sepsis remains a leading cause of morbidity and mortality worldwide.